1984
DOI: 10.1002/pen.760241411
|View full text |Cite
|
Sign up to set email alerts
|

Changes in yield and deformation of polycarbonates caused by physical aging

Abstract: Change in yield and deformation associated with physical aging was studied on a series of polycarbonates (bisphenol-A polycarbonate, polyestercarbonates, and phenolphthalein-bisphenol-A copolycarbonates) and a polysulfone. A combination of tensile and biaxial yield measurements, dynamical mechanical analysis, and high-resolution density measurements were performed. These data indicate that both free volume arguments and molecular entanglement arguments are inadequate for explaining the differences in large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 20 publications
5
35
0
Order By: Relevance
“…12 The most commonly encountered method to obtain the pressure dependence µ is by measuring the strain rate dependence of the yield stress in different loading geometries (e.g., uniaxial, or planar, tension and compression, shear, etc.). 28,38,39 The disadvantage of this method is that each geometry requires its own, optimized, sample shape and dimensions. In particular the latter can have a strong influence on the thermal history during processing, making it difficult to prepare samples with identical S a values for different loading geometries, which is essential to obtain a correct value for µ.…”
Section: Characterization Of Intrinsic Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…12 The most commonly encountered method to obtain the pressure dependence µ is by measuring the strain rate dependence of the yield stress in different loading geometries (e.g., uniaxial, or planar, tension and compression, shear, etc.). 28,38,39 The disadvantage of this method is that each geometry requires its own, optimized, sample shape and dimensions. In particular the latter can have a strong influence on the thermal history during processing, making it difficult to prepare samples with identical S a values for different loading geometries, which is essential to obtain a correct value for µ.…”
Section: Characterization Of Intrinsic Behaviormentioning
confidence: 99%
“…25 Increasing the amount of softening by increasing the yield stress, on the other hand, e.g., by annealing, leads to severe localization of strain and can even induce brittle fracture in (relatively low molecular weight) polycarbonate. 20,[26][27][28] In modeling practice and in experiments, it is usually assumed that the initial age exceeds the experimental time which implies that material properties do not change and are time invariant during the test. In the case of long-term loading conditions, or conditions where accelerated aging can be expected, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since polymeric materials often display pressure sensitivity [Bubeck et al 1984;Quinson et al 1997;Rottler and Robbins 2001], this was investigated by means of a Drucker-Prager elastic-plastic material. The pressure sensitivity of a Drucker-Prager material is characterised by (together with the standard assumptions in von Mises plasticity) a parameter known as the friction angle, α, allowing the yield stress to vary with the mean stress σ m .…”
Section: 3mentioning
confidence: 99%
“…They associated the validity of the pmT criterion with the occurrence of shear bands. However, Bubeck et al [10] measured a larger number of yield points for PC and found that they fit the pmvM criterion. This discrepancy may be due to the use of different yield point definitions in the two studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several different definitions of the yield point have been employed to determine the yield stress. Most authors [7,9,10] take the maximum of the stress-strain curve as the yield stress. The offset-stress [11] is also used, particularly when the stress-strain curve exhibits no clear maximum.…”
Section: Introductionmentioning
confidence: 99%